2010
DOI: 10.2166/hydro.2010.107
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pile group scour in waves using support vector machines and ANN

Abstract: Scour around pile groups is rather complicated and not yet fully understood due to the fact that it arises from the triple interaction of fluid-structure-seabed. In this study, two data mining approaches, i.e. Support Vector Machines (SVM) and Artificial Neural Networks (ANN), were applied to estimate the wave-induced scour depth around pile groups. To consider various arrangements of pile groups in the development of the models, datasets collected in the field and laboratory studies were used and arrangement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…These methods have been recently used in different fields of engineering problems representing promising performance compared to the other soft computing methods (e.g. Ghazanfari-Hashemi et al 2011;Grbićet al 2013;Sun et al 2014;Roushangar & Koosheh 2015;Roushangar et al 2016;Najafzadeh & Oliveto 2020). To the best of authors' knowledge, SVR and GPR methods have not been implemented for the prediction of the mean wave overtopping rate so far.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been recently used in different fields of engineering problems representing promising performance compared to the other soft computing methods (e.g. Ghazanfari-Hashemi et al 2011;Grbićet al 2013;Sun et al 2014;Roushangar & Koosheh 2015;Roushangar et al 2016;Najafzadeh & Oliveto 2020). To the best of authors' knowledge, SVR and GPR methods have not been implemented for the prediction of the mean wave overtopping rate so far.…”
Section: Introductionmentioning
confidence: 99%
“…Raikar et al (2016) applied ANN and genetic algorithms (GA) for prediction of scour depth within channel contractions. Many researchers also verified the efficacy of techniques like adaptive neuro-fuzzy inference system (ANFIS) and support vector machines (SVM) for predicting bridge scour (Bateni et al 2007;Muzzammil 2010;Ghazanfari-Hashemi et al 2011;Pal et al 2011;Hong et al 2012;Akib et al 2014;Khan et al 2014;Najafzadeh et al 2016;Chou & Pham 2017). More recently, several studies have reported the use of hybrid techniques for predicting bridge scour (Chou & Pham 2014;Jannaty et al 2015;Dang et al 2019).…”
Section: Introductionmentioning
confidence: 95%
“…They are used in the fields of prediction and classification, fields in which regression models and other related statistical techniques have traditionally been used [1][2][3][4]. Multilayer perceptron neural networks (MLPs) are one of the architectures of ANNs acting as a type of regression model, not necessarily parametric, which enables complex functional forms to be modeled [5,6].…”
Section: Introductionmentioning
confidence: 99%